2006
DOI: 10.1016/j.nima.2006.05.063
|View full text |Cite
|
Sign up to set email alerts
|

A noiseless kilohertz frame rate imaging detector based on microchannel plates read out with the Medipix2 CMOS pixel chip

Abstract: A new hybrid imaging detector is described that is being developed for the next generation adaptive optics (AO) wavefront sensors. The detector consists of proximity focused microchannel plates (MCPs) read out by pixelated CMOS application specific integrated circuit (ASIC) chips developed at CERN ("Medipix2"). Each Medipix2 pixel has an amplifier, lower and upper charge discriminators, and a 14-bit counter. The 256 x 256 array can be read out noiselessly (photon counting) in 286 µs. The Medipix2 is buttable o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…It demonstrated that the acquisition of mass spectrometric images is possible with ion detection using front-end digitization and highly pixilated sensors. The Timepix offers the capability of high event rates up to 4 kHz [21] and allows very fast data acquisition with an appropriate interface for data transfer. The experimental setup presented here was not optimized for fast data acquisition, since more advanced USB-based readout modules are currently being developed [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It demonstrated that the acquisition of mass spectrometric images is possible with ion detection using front-end digitization and highly pixilated sensors. The Timepix offers the capability of high event rates up to 4 kHz [21] and allows very fast data acquisition with an appropriate interface for data transfer. The experimental setup presented here was not optimized for fast data acquisition, since more advanced USB-based readout modules are currently being developed [22].…”
Section: Discussionmentioning
confidence: 99%
“…The Timepix offers the capability of high event rates up to 4 kHz [21] and allows very fast data acquisition with an appropriate interface for data transfer. The experimental setup presented here was not optimized for fast data acquisition, since more advanced USB-based readout modules are currently being developed [22].…”
Section: Discussionmentioning
confidence: 99%
“…The time over threshold output is directly proportional to the amount of charge deposited on the particular pixel, i.e., to the energy of the detected particle. This is an option that is very important when centroiding algorithms are applied to achieve subpixel spatial resolution for events that lead to a detectable signal over a range of pixels, such as the signals that can be detected when electron or ion signals are first amplified using a mcirochannel plate detector placed in front of the Timepix detector, 26,27 as will be further explained in a later paragraph.…”
Section: The Medipix/timepix Chipsmentioning
confidence: 99%
“…Depending on the distance and extraction voltage between the MCP and the Timepix ASIC, the charge cloud coming from the MCP will cover multiple pixels. Using the above-mentioned ability to determine the amount of charge deposited per pixel, a weighted centroiding algorithm can be used to achieve spatial resolution well below 10 m. 27 In this case the size of the MCP pores becomes the limiting factor. A similar technique has been known and applied also in VMI measurements for quite some time.…”
Section: High Position Resolution Measurementsmentioning
confidence: 99%
“…The Medipix and Timepix [1] application specific integrated circuits (ASICs) are pixelated devices (256 × 256) where each pixel has an amplifier and discriminator network that can count individual charge pulses, and in the case of the Timepix, also measure the time of arrival or amplitude of the charge event. These ASICs can be used to readout imaging microchannel plates, whose output electron charge pulses represent information such as the spatial location and time of arrival of the stimulating input quanta (photons [2], electrons [3], neutrons [4] or ions [5]. The main advantages of these ASIC readouts of MCPs is their very low amplifier noise, (∼ 75 electrons rms), allowing for the operation of the MCP(s) at low gains (< 10000) thereby extending their lifetime at high input rates as well as high local rates.…”
mentioning
confidence: 99%